2014
DOI: 10.3945/ajcn.114.089656
|View full text |Cite
|
Sign up to set email alerts
|

Added sugars and periodontal disease in young adults: an analysis of NHANES III data

Abstract: A high frequency of consumption of added sugars is associated with periodontal disease, independent of traditional risk factors, suggesting that this consumption pattern may contribute to the systemic inflammation observed in periodontal disease and associated noncommunicable diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 29 publications
0
109
2
2
Order By: Relevance
“…As a categorical variable, three groups were created based on tertile distributions of total added sugars intake separately for men and women, because previous studies suggested a dose–response of added sugars intake on health outcomes, such as cardiovascular disease mortality 7 and poor oral health. 9 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a categorical variable, three groups were created based on tertile distributions of total added sugars intake separately for men and women, because previous studies suggested a dose–response of added sugars intake on health outcomes, such as cardiovascular disease mortality 7 and poor oral health. 9 …”
Section: Methodsmentioning
confidence: 99%
“…3 Many studies have shown that high consumption of added sugars (eg, >10% of total daily calories from added sugars) is associated with adverse health outcomes in adults, including obesity/weight gain, 4,5 type 2 diabetes, 6 cardiovascular disease, 7,8 and periodontal disease. 9 …”
mentioning
confidence: 99%
“…To the best of our knowledge, no previous epidemiological study has explored the association between soft drink consumption and periodontal status in pregnancy. Sugar‐sweetened beverage consumption and other sources of added sugars have been associated with increased probing depth in non‐pregnant women. Soft drink consumption was associated with periodontal disease defined by community periodontal index ≥3 mm or as loss of attachment ≥1 mm in middle‐aged adults, in a dose–response relationship …”
Section: Discussionmentioning
confidence: 99%
“…The consumption of sweetened beverages has been associated with increased probing depth . Recently, consumption of added sugars has also been associated with increased probing depth in young adults in a representative study of the United States population …”
Section: Introductionmentioning
confidence: 99%
“…[39,38] In periodontal disease, destruction of the connective tissue for the most part, comes about because of the association of microscopic organisms (bacteria); their items & their products with mononuclear cells. [40,41,42] Α number of studies have shown that there is а wide range of systemic risk factors for periodontаl disease; these elements incorporate overweight/obesity, tobacco smoking, respiratory diseases, diabetes mellitus, rheumatoid arthritis, osteoporosis, cardiovascular disorders, kidney diseases, and dementia. [43,44] Other medical diseases such as certain types of cancer, ΑӀDS, defective dental restoration's medication use.…”
Section: Introductionmentioning
confidence: 99%